Sharing Food, coordinado por Eric de Garine, María Luz Rodrigo, Christine Raimond y F. Xavier Medina: Sharing Food. Eric de Garine, María Luz Rodrigo, Christine Raimond and F. Xavier Medina, eds. - Cantarero Abad, Luis (Studium, 2018)
Review: ‘Sharing Food.’ Eric de Garine, María Luz Rodrigo, Christine Raimond and F. Xavier Medina, coords.Guadalajara (Jalisco), Centro Universitario de Ciencias Sociales y Humanidades, Universidad de Guadalajara, 2016.(Colección Estudios del Hombre. Serie Antropología de la Alimentación). 299 p., ils. ISBN 9786077425557.Key words: food, sharing food, anthropology of food, food history, cultural and social anthropology.
Keywords: food; sharing food; anthropology of food; food history; cultural and social anthropology; Eric de Garine; María Luz Rodrigo Estevan; Christine Raimond; F. Xavier Medina